PELATIHAN DAN EDUKASI BELANJA ONLINE YANG HEMAT DAN AMAN DENGAN MENGGUNAKAN SITUS E-COMMERCE BERBASIS PROMOSI DAN DISKON - Ahmad Munir Hamid (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2022)
This study aims to explore the impact of promotional and discount strategies on online shopping decisions on e-commerce platforms. The growth of shopping through e-commerce platforms has opened up great opportunities for businesses to expand their marketing reach. Marketing through e-commerce platforms can also be done through various social media applications. With many businesses utilizing various social media platforms for promotion, competition in the business world is getting fiercer. Online shopping has become a popular trend among consumers, and e-commerce sites use various promotional strategies and discounts to attract consumers. However, research specifically exploring the impact of promotional and discount strategies on consumer behavior in the context of online shopping is limited. In this study, the method applied is the study of literature. Research findings show that promotional and discount strategies have a significant impact on online purchasing attitudes on e-commerce platforms. Attractive promotions and large discounts have been proven to increase the frequency of purchases by consumers. In addition, promotions and discounts also have a positive influence on consumer intentions to return to make purchases on the e-commerce platform.